Method Development and Validation with Statistical Analysis to Access Raspberry Ketone Metabolism in Mice by UHPLC-QqQ-MS/MS. (29th May 2020) - Yuan, Bo; Zhao, Danyue; Kshatriya, Dushyant; Bello, Nicholas; Simon, James; Wu, Qingli
Abstract: Objectives: Raspberry ketone (4-(4-hydroxyphenyl)-2-butanone) (RK) is the major aroma compound of red raspberries and used commercially as flavoring agent. It is now gaining attention as a weight loss supplement. This work aimed to establish atargeted ultra-high performance liquid chromatography triple quadrupole tandem mass spectrometry (UHPLC-QqQ-MS/MS) method for analysis of raspberry ketone and its 25 associated metabolites in mouse plasma and brain. Methods: Dispersion and projection analysis and central composite design were used for LC-MS method optimization. Random effect analysis of variance was applied for validation inference and variation partition. Within this framework, repeatability, a broader sense of precision, was calculated as fraction of accuracy variance, reflecting instrumental imprecision, compound degradation and carry-over effects. Multivariate correlation analysis and principle component analysis were conducted, revealing underlying interlinkage and association among the manifold of method traits. R programming was engaged in streamlined statistical analysis and data visualization. Results: The developed and validated method for RK and 25 metabolites had accuracy, matrix effect, recovery and processing efficiency bound mostly within the 80∼120% range, precision error below 5%, limit of quantification at 0.4∼6.0 ng/mL and linear range across three orders of magnitude. Two particular phenomena, the analytes' background existence in the enzyme solution used for phase II metabolites deconjugation, and the noted liability of analytes in pure solvent at 4 °C vs. elevated stability in biomatrices, were found critical to method development and validation. Conclusions: The UHPLC-QqQ-MS/MS method developed and validated provided an important tool for further investigation of RK metabolism and bioavailability. Funding Sources: National Institutes of Health.